Comparison of various 3D printed and milled PAEK materials: Effect of printing direction and artificial aging on Martens parameters. Issue 2 (February 2020) - Prechtel, Alexander; Reymus, Marcel; Edelhoff, Daniel; Hickel, Reinhard; Stawarczyk, Bogna
Abstract: Objectives: The aim of this study was to investigate the effect of artificial aging on the Martens parameters of different 3D printed and milled polyaryletherketon (PAEK) materials. Methods: In total 120 specimens of 4 different polyetheretherketon (PEEK) materials (Essentium PEEK, KetaSpire PEEK MS-NT1, VICTREX PEEK 450 G and VESTAKEEP i4 G) were additively manufactured via fused layer manufacturing (FLM) in either horizontal or vertical directions (n = 15 per group). 75 specimens were milled out of prefabricated PAEK blanks from the materials breCAM.BioHPP, Dentokeep, JUVORA Dental Disc 2 and Ultaire AKP ( = 15 per group). Martens hardness (HM), indentation hardness (HIT ) and indentation modulus (EIT ) were determined initially and longitudinally after thermocycling (5−55 °C, 10, 000x) and autoclaving (134 °C, 2 bar). In each case, the surface topography of the specimens was examined for modifications using a light microscope. Data were analysed with Kolmogorov-Smirnov test, univariate ANOVA followed by post-hoc Scheffé test with partial eta squared (ηp 2 ), Kruskal–Wallis-, Mann–Whitney-U-, Friedman- and Wilcoxon-Test. A value of p < 0.05 was considered as significant. Results: Milled specimens showed higher Martens parameters than printed ones (p < 0.001). Artificial aging had a negative effect on the measured parameters (p < 0.001). Horizontally printed specimens presented higher Martens parameters than vertically printed ones, regardless of material and aging process (p < 0.001). Essentium PEEK and breCAM.BioHPP showed the highest and VICTREX PEEK 450G as well as Ultaire AKP the lowest values of all investigated PAEK materials initially, after thermocycling and after autoclaving (p < 0.001). Microscopic examinations showed that artificial aging did not cause any major modifications of the materials. Significance: Additively manufactured PEEK materials showed lower Martens parameters than milled ones, whereas horizontally printed specimens presented higher values than vertically printed ones. Artificial aging had a negative effect on the Martens parameters, but not on the surface topography.